A simplified model to predict thermo-hygral behaviour and explosive spalling of concrete - Liu, Jin-Cheng (2020)
Explosive spalling of concrete leads to premature failure of concrete structures under fire. Thus it is important to assess explosive spalling risk of concrete. Thermo-hygral process in concrete is believed to be responsible for explosive spalling of concrete. Currently, simple yet reliable models to predict thermo-hygral behaviour are still desirable. In this study, a one-dimensional numerical model is established to predict moisture migration, pore pressure and explosive spalling in concrete exposed to heating. The effectiveness of the model is validated against five sets of experimental data. The experiments covered (a) moisture migration inside normal strength concrete (NSC); (b) pore pressure buildup inside NSC; (c) pore pressure buildup inside high-performance concrete (HPC) containment vessel; (d) pore pressure buildup inside HPC slab; and (e) one-time explosive spalling of concrete. The results predicted by the model match well the experimental results. The model developed provides an effective and economical tool to assess explosive spalling of concrete in addition to experimental methods.